In Vitro and In Vivo Bactericidal and Antibiofilm Efficacy of Alpha Mangostin Against Staphylococcus aureus Persister Cells - Felix, LewisOscar; Mishra, Biswajit; Khader, Rajamohammed; Ganesan, Narchonai; Mylonakis, Eleftherios (Frontiers in Cellular and Infection Microbiology, 2022)
The formation of persister cells is associated with recalcitrance and infections. In this study, we examined the antimicrobial property of alpha mangostin, a natural xanthone molecule, against methicillin-resistant Staphylococcus aureus (MRSA) persisters and biofilm. The MIC of alpha mangostin against MRSA persisters was 2 µg/ml, and activity was mediated by causing membrane permeabilization within 30 min of exposure. The membrane activity of alpha mangostin was further studied by fast-killing kinetics of MRSA persiste r cells and found that the compound exhibited 99.99% bactericidal activity within 30 min. Furthermore, alpha mangostin disrupted established MRSA biofilms and inhibited bacterial attachment as biofilm formation. Alpha mangostin down-regulated genes associated with the formation of persister cells and biofilms, such as norA, norB, dnaK, groE, and mepR, ranging from 2 to 4-folds. Alpha mangostin at 16 μg/ml was non-toxic (> 95% cell survival) to liver-derived HepG2 and lung-derived A549 cells, similarly. Still, alpha mangostin exhibited 50% cell lysis of human RBC at 16 μg/ml. Interestingly, alpha mangostin was effective in vivo at increasing the survival up to 75% (p<0.0001) of Galleria mellonella larvae infected with MRSA persister for 120 h. In conclusion, we report that alpha mangostin is active against MRSA persisters and biofilms, and these data further our understanding of the antistaphylococcal activity and toxicity of this natural compound.